Vinyl records and analog culture in the digital age : pressing matters - Winters, Paul E. (Lexington Books, 2016)
Analog Culture in the Digital Age: Pressing Matters looks at music technologies from a popular culture studies perspective, taking into consideration the ways in which human beings bring these technologies into their lives and the discursive practices they create. Focusing on the resurgence of vinyl records, this book examines the ways in which interacting with analog technologies creates and shapes listening subjectivity in its users.